ОҚЫЎШЫЛАР МЕНЕН ЭТЮД ҮСТИНДЕ ИСЛЕЎ ҲӘМ ТЕХНИКАЛЫҚ ТӘРЕПИН РАЎАЖЛАНДЫРЫЎ УСЫЛЛАРЫ - Жуманиязов, И.Р. (FAN va JAMIYAT, 2024)
The article discusses a wide range of topics, including playing musical instruments, practicing etudes and performance techniques, exploring teaching approaches between students and instructors, and delving into the world of performing arts.